Learning Continuity during COVID-19: An Analysis of the Higher Education Sector of Bangladesh - Mukherjee, Debarshi; Hasan, Khandakar Kamrul (Journal of Education Culture and Society, 2023)
Aim. This study aims to understand the factors determining university students’ behavioural intentions toward online learning in Bangladesh. Specifically, this study investigates the relationship between performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), and behavioural intention (BI). Moreover, this study explores the influence of pandemic fear (PF) as a moderator in the relationship between exogenous and endogenous factors.Methods. The study is cross-sectional and followed a quantitative research approach with purposive sampling. Data were collected at a single point using a sample size of 578 respondents who studied online during the various phases of lockdown at five public and five private universities in Bangladesh. Regarding multivariate analysis, the Partial Least Squares - Structural Equation Modeling (PLS-SEM) is applied in this study to test the causal relationships in the structural model, as it is considered a second-generation technique.Results. Statistically, a positive significance was found between PE, EE, SI, and BI in online learning participation. Whereas the FC and the BI exhibited a negative relationship, a positive relationship was found between PE, EE, and the SI on BI. In addition, a moderating role for PF was investigated, and EE and FC were found to influence BI significantly.Conclusion. This study presents an extended UTAUT model by integrating pandemic fear as the moderator to study students' behavioural intention to adopt an online learning system under a disruptive situation. Practitioners, especially academicians and policymakers, will find this model useful while developing andragogic interventions for the higher education sector in Bangladesh.